2022
DOI: 10.1002/cpdd.1174
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of Intravenous Doses of PF‐07304814, a Phosphate Prodrug Protease Inhibitor for the Treatment of SARS‐CoV‐2, in Healthy Adult Participants

Abstract: Studies on targeted antivirals for treatment of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the cause of the ongoing pandemic, are limited. PF‐07304814 (lufotrelvir) is the phosphate prodrug of PF‐00835231, a protease inhibitor targeting the 3C‐like protease of SARS‐CoV‐2. This phase 1 study evaluated the safety, tolerability, and pharmacokinetics (PK) of single ascending intravenous doses of lufotrelvir (continuous 24‐hour infusion of 50, 150, 500, or 700 mg) versus placebo in healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Subsequently, good laboratory practice data from 2-week continuous infusion toxicology studies in rats and monkeys became available to support the enrollment of participants in MAD. A study in healthy volunteers was also initiated (C4611007) that provided data to inform a starting MAD dose for C4611001 [ 21 ]. The notable finding in the monkey study was an exacerbation at higher doses of commonly observed infusion procedure‒related effects of inflammation and thromboemboli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, good laboratory practice data from 2-week continuous infusion toxicology studies in rats and monkeys became available to support the enrollment of participants in MAD. A study in healthy volunteers was also initiated (C4611007) that provided data to inform a starting MAD dose for C4611001 [ 21 ]. The notable finding in the monkey study was an exacerbation at higher doses of commonly observed infusion procedure‒related effects of inflammation and thromboemboli.…”
Section: Discussionmentioning
confidence: 99%
“…After a single 500-mg dose of lufotrelvir, the maximum plasma concentration, C ss , and area under the curve for PF-00835231 were higher among participants in this study compared with healthy volunteers, whereas t ½ was similar between healthy participants and patients [ 21 ]. However, the small number of participants in this study preclude definitive comparisons between the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation